A MOF-based electrocatalytic material and preparation method thereof

The preparation of Fe/Co/Ni-MOFs catalysts by mechanical ball milling solves the problems of rare and high cost of precious metal catalysts, and realizes efficient electrocatalytic oxygen evolution reaction, providing excellent electrocatalytic activity and low-cost solutions.

CN115652325BActive Publication Date: 2025-01-14ZHEJIANG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211207775.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-30
Publication Date
2025-01-14
Estimated Expiration
2042-09-30

AI Technical Summary

Technical Problem

Existing precious metal catalysts such as iridium dioxide and ruthenium dioxide have rare and high cost problems in electrocatalytic oxygen evolution reactions, and have low catalytic efficiency, making it difficult to meet the needs of large-scale applications.

Method used

Fe/Co/Ni-MOFs catalyst is prepared by mechanical ball milling method using inorganic salts and metal organic framework materials, and the process parameters and raw material types are optimized to form high-active and stable electrocatalytic materials. Fe-based MOFs such as MIL-53 are not damaged without damage Its structure enhances catalytic activity.

Benefits of technology

It realizes an efficient electrocatalytic oxygen evolution reaction, with an overpotential of only 180mV when the current density is 10mA cm-2. The material has excellent electrocatalytic activity, and the preparation process is simple and easy to perform, with low cost, and is suitable for mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003873460110000011
    Figure HDA0003873460110000011
  • Figure HDA0003873460110000012
    Figure HDA0003873460110000012
  • Figure HDA0003873460110000021
    Figure HDA0003873460110000021
Patent Text Reader

Abstract

The present invention provides an electrocatalytic material based on MOF and a preparation method thereof. MIL-53 with a clear original morphology and uniform particle size is mixed with Ni and Co-based inorganic salts by a mechanical ball milling method, so that oxygen vacancies are generated in MIL-53 and the surface of MIL-53 is modified without completely destroying its crystal structure, thereby improving the electrocatalytic oxygen evolution ability. The present invention is simple, easy to operate, low in cost, and can be mass-produced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy materials and relates to an MOF-based electrocatalytic material and a preparation method thereof. Background Art

[0002] At present, the global demand for energy and the consumption of fossil fuels have greatly increased. With the proposal of the national "dual carbon" goal, the demand for green innovative technologies such as low-carbon, zero-carbon and negative-carbon technologies has gradually increased. At this stage, green innovative technologies include water electrolysis to produce hydrogen, fuel cells, etc., one of the key steps of which is the electrocatalytic oxygen evolution reaction (OER). However, due to the high energy level barriers and slow reaction kinetics of this reaction, efficient electrocatalysts are required to drive the reaction, thereby reducing the energy level barriers and increasing the reaction rate. At present, the precious metal catalysts iridium dioxide and ruthenium dioxide (RuO2) are the main commercial OER electrocatalysts, but their limited sources and high manufacturing costs greatly limit large-scale practical applications. How to prepare cheap and efficient electrocatalytic materials in large quantities is an urgent problem to be solved.

[0003] Therefore, scientists have invested tremendous efforts in developing a variety of OER electrocatalysts or catalyst precursors, such as transition metal oxides, hydroxides, oxyhydroxides, sulfides, phosphides, and metal-organic frameworks. A large number of studies have shown that the real active substances are oxyhydroxides and hydroxides. The performance of such materials has been greatly optimized through the control and regulation of dimensions, morphology, size, defects, crystal engineering, etc. However, these materials still cannot meet the needs of industrial production. Metal-organic frameworks (MOFs) have high specific surface area and high activity, and have a variety of metal centers and coordination modes, as well as functionalization of organic ligands, which make them highly chemically and structurally selective. They can be used as electrocatalyst precursors in alkaline environments to achieve efficient OER catalysis. During the electrocatalytic process, the surface of MOFs materials will preferentially transform to form an oxyhydroxide layer. Due to the discrete metal sites, porosity, and the presence of ligands of MOFs, the formed oxyhydroxides have many defect structures, thereby obtaining more highly active sites and achieving efficient OER electrocatalysis. In order to improve and optimize the catalytic activity, it is usually necessary to carry out in a multi-metal catalytic system. Therefore, the introduction of multi-metals usually leads to changes in the morphology and structure of MOFs and changes in yield. The preparation of bimetallic and multi-metallic MOFs materials by chemical synthesis will lead to changes in their morphology and crystal structure and even reduce their yield. Therefore, we propose to prepare Fe / Co / Ni-MOFs materials by mechanical ball milling of Ni and Co-based inorganic salts with Fe-based MOFs, and further enhance the catalytic activity of Fe / Co / Ni-MOFs without completely destroying the MOFs structure. Summary of the invention

[0004] The present invention provides an electrocatalytic material based on MOF and a preparation method thereof. In the method, an Fe / Co / Ni-MOFs catalyst is prepared by mechanical ball milling of an inorganic salt and a metal organic framework material, and process parameters and types of raw materials in the preparation process are selected and optimized, thereby solving the problems of scarcity, high price and low catalytic efficiency of traditional noble metal catalysts.

[0005] In order to achieve the above object, the technical solution of the present invention is as follows:

[0006] The present invention provides an electrocatalytic material based on MOF. In an environment where an inert gas is introduced, a mixed powder of MOFs and metal inorganic salts is subjected to a mechanical ball milling method to obtain a highly active and stable electrocatalytic OER material. The above-mentioned Fe-based MOFs include MIL-53, MIL-88A, MIL-88B, MIL-100, MIL-101, NH2-MIL-53, NH2-MIL-88B and NH2-MIL-101, etc., and it is found through SEM and HRTEM characterization that the original structure of MOFs is not completely destroyed. After various electrochemical tests, the performance is significantly improved, among which the performance of MIL-53 is the best. The performance of the Fe-based MOFs after ball milling with other metal salts of the present invention is better than that of untreated Fe-based MOFs.

[0007] Specifically, an electrocatalytic material based on MOF is prepared by the following method:

[0008] The Fe-based MOFs are placed at 100-200° C. (preferably 150° C.) for 1-24 h (preferably 12 h) for activation to obtain activated Fe-based MOFs; under a protective atmosphere, the activated Fe-based MOFs, nickel salt and cobalt salt are ball-milled at 300-1500 rpm (preferably 1000 rpm) for 30-180 min (preferably 60 min); the obtained powder is subjected to post-treatment A to obtain the MOF-based electrocatalytic material;

[0009] The mass ratio of the activated Fe-based MOFs, nickel salt and cobalt salt is 1:0.5-2:0.5-2 (preferably 1:1:1).

[0010] Furthermore, the protective atmosphere is argon, nitrogen or helium (preferably argon).

[0011] The metal ion type of inorganic salts cannot be replaced because Ni and Co are first transition metals with empty d orbitals, which can easily absorb electrons to form complexes. Other transition metal sources such as copper are less active in OER and are not used.

[0012] Furthermore, the nickel salt is one or a mixture of two or more of anhydrous nickel chloride, nickel acetate tetrahydrate, nickel nitrate hexahydrate, and nickel chloride hexahydrate (preferably nickel acetate tetrahydrate); the cobalt salt is one or a mixture of two or more of cobalt acetate tetrahydrate, cobalt nitrate hexahydrate, and cobalt chloride hexahydrate (preferably cobalt nitrate hexahydrate).

[0013] Furthermore, the post-treatment A is: centrifuging the powder with ethanol, washing the obtained precipitate with N,N-dimethylformamide (once), washing it with ethanol (twice), and drying it at (60°C) (12h) to obtain the MOF-based electrocatalytic material.

[0014] Furthermore, the Fe-based MOFs are one of MIL-53, MIL-88A, MIL-88B, MIL-100, MIL-101, NH2-MIL-53, NH2-MIL-88B, NH2-MIL-101, or a mixture of two or more thereof.

[0015] In an embodiment of the present invention, the Fe-based MOFs is MIL-53.

[0016] The invention provides a preparation method of MIL-53. The method comprises the following steps: adding FeCl3·6H2O and terephthalic acid (BDC) into N,N-dimethylformamide (DMF), stirring the mixture at room temperature for 30 min-3 h (preferably 1 h), pouring the obtained mixed solution into a reaction kettle with a polytetrafluoroethylene liner, reacting the mixture at 150°C for 2-48 h (preferably 6 h), adding deionized water into the obtained suspension, stirring the mixture at 300-1000 rpm (preferably 600 rpm) for 5-24 h (preferably 12 h), and subjecting the obtained mixed solution to post-treatment B to obtain MIL-53. The molar ratio of the FeCl3·6H2O to the terephthalic acid is 1:0.5-2 (preferably 1:1).

[0017] Furthermore, the volume of the N,N-dimethylformamide is 2 mL / mmol-15 mL / mmol (preferably 5 mL / mmol) based on the amount of terephthalic acid, and the volume of the deionized water is 50 mL / mmol-500 mL / mmol (preferably 150 mL / mmol) based on the amount of FeCl3·6H2O.

[0018] The present invention recommends an activation temperature of 100-200° C. Too high a temperature will cause the MOFs structure to be destroyed, while too low a temperature will result in insufficient activation.

[0019] Furthermore, the post-treatment B is: centrifuging the mixed solution, washing the obtained precipitate with N,N-dimethylformamide (twice) and ethanol (three times) in sequence, and then freeze-drying to obtain the MIL-53.

[0020] The letters A and B in post-processing are just to distinguish different stages of post-processing and have no special meaning.

[0021] The present invention also provides an application of the above MOF-based electrocatalytic material in an electrocatalytic reaction. Preferably, the electrocatalytic reaction is an electrocatalytic oxygen evolution reaction.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The original MIL-53 with clear morphology and uniform particle size is mixed with Ni and Co-based inorganic salts by mechanical ball milling, so that oxygen vacancies are generated in MIL-53 and its surface is modified without completely destroying the crystal structure of MIL-53, thereby improving the electrocatalytic oxygen evolution ability. The present invention is simple, easy to operate, low in cost, and can be mass-produced. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a scanning electron microscope image of MIL-53 in Example 1.

[0025] Figure 2 This is a scanning electron microscope image of sample 1 in Example 2.

[0026] Figure 3 This is the transmission electron microscope image of sample 1 in Example 2.

[0027] Figure 4 This is a scanning electron microscope image of sample 3 in Example 4.

[0028] Figure 5 This is a scanning electron microscope image of sample 6 in Example 7.

[0029] Figure 6 This is the electrocatalytic performance diagram of sample 1, sample 2, sample 3, sample 4, sample 5, sample 6, and RuO2.

[0030] Figure 7 These are the electrochemical impedance spectra of sample 1, sample 2, sample 3, sample 4, sample 5, sample 6, and RuO2. DETAILED DESCRIPTION

[0031] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.

[0032] Embodiment 1:

[0033] MIL-53 was synthesized by solvothermal method. 541 mg (2 mmol) FeCl3·6H2O and 332 mg (2 mmol) BDC were added to 10 mL N,N-dimethylformamide and stirred at room temperature for 1 h. The resulting mixed solution was poured into a reactor lined with polytetrafluoroethylene for a high temperature reaction at 150 ° C for 6 h. After the reaction was completed, the reactor was naturally cooled and the reaction suspension was added to a glass bottle. 300 mL of deionized water was added and stirred for 12 h (600 rpm). The resulting mixed solution was centrifuged, washed twice with DMF and three times with ethanol, and then freeze-dried to obtain MIL-53.

[0034] Embodiment 2:

[0035] The MIL-53 prepared according to the method in Example 1 was placed in a vacuum oven for activation at 150°C for 12 hours. After the reaction was completed, 150 mg (0.60 mmol) of Ni(CH3COO)2·4H2O, 150 mg (0.53 mmol) of Co(NO3)2·6H2O and 150 mg of activated MIL-53 were added to the ball mill, the ball mill was sealed and evacuated, argon was introduced and this operation was repeated 3 times, and then the ball mill was milled in a ball mill for 1 hour (1000 rpm) to obtain a precursor powder; ethanol was added to the precursor powder and centrifuged, and the obtained precipitate was then centrifuged and washed once with N,N-dimethylformamide and twice with ethanol, and then dried at 60°C for 12 hours to obtain sample 1.

[0036] Embodiment 3:

[0037] The MIL-53 prepared according to the method in Example 1 was placed in a vacuum oven for activation at 150°C for 12 hours. After the reaction was completed, 150 mg (0.60 mmol) of Ni(CH3COO)2·4H2O, 150 mg (0.60 mmol) of Co(CH3COO)2·4H2O and 150 mg of activated MIL-53 were added to a ball mill. The ball mill was sealed and evacuated, and argon was introduced and this operation was repeated 3 times. The ball mill was then milled in a ball mill for 1 hour (1000 rpm) to obtain a precursor powder. Ethanol was added to the precursor powder and centrifuged. The resulting precipitate was then centrifugally washed once with N,N-dimethylformamide and twice with ethanol, and then dried at 60°C for 12 hours to obtain sample 2.

[0038] Embodiment 4:

[0039] The MIL-53 prepared according to the method in Example 1 was placed in a vacuum oven for activation at 150°C for 12 hours. After the reaction was completed, 150 mg (0.60 mmol) of Ni(CH3COO)2·4H2O, 150 mg (0.63 mmol) of CoCl2·6H2O and 150 mg of activated MIL-53 were added to a ball mill. The ball mill was sealed and evacuated, and argon was introduced and this operation was repeated 3 times. The ball mill was then ball milled in a ball mill for 1 hour (1000 rpm) to obtain a precursor powder. Ethanol was added to the precursor powder and centrifuged. The resulting precipitate was then centrifugally washed once with N,N-dimethylformamide and twice with ethanol, and then dried at 60°C for 12 hours to obtain sample 3.

[0040] Embodiment 5:

[0041] The MIL-53 prepared according to the method in Example 1 was placed in a vacuum oven for activation at 150°C for 12 hours. After the reaction was completed, 150 mg (0.63 mmol) of NiCl2·6H2O, 150 mg (0.52 mmol) of Co(NO3)2·6H2O and 150 mg of activated MIL-53 were added to a ball mill. The ball mill was sealed and evacuated, and argon was introduced and this operation was repeated 3 times. Then, the ball mill was milled in a ball mill for 1 hour (1000 rpm) to obtain a precursor powder. Ethanol was added to the precursor powder and centrifuged. The resulting precipitate was then centrifugally washed once with N,N-dimethylformamide and twice with ethanol, and then dried at 60°C for 12 hours to obtain sample 4.

[0042] Embodiment 6:

[0043] The MIL-53 prepared according to the method in Example 1 was placed in a vacuum oven for activation at 150°C for 12 hours. After the reaction was completed, 150 mg (0.63 mmol) of NiCl2·6H2O, 150 mg (0.60 mmol) of Co(CH3COO)2·4H2O and 150 mg of activated MIL-53 were added to a ball mill. The ball mill was sealed and evacuated, and argon was introduced and this operation was repeated 3 times. Then, the ball mill was milled in a ball mill for 1 hour (1000 rpm) to obtain a precursor powder. Ethanol was added to the precursor powder and centrifuged. The obtained precipitate was then centrifuged and washed once with N,N-dimethylformamide and twice with ethanol, and then dried at 60°C for 12 hours to obtain sample 5.

[0044] Embodiment 7:

[0045] The MIL-53 prepared according to the method in Example 1 was placed in a vacuum oven for activation at 150°C for 12 hours. After the reaction was completed, 150 mg (0.63 mmol) of NiCl2·6H2O, 150 mg (0.63 mmol) of CoCl2·6H2O and 150 mg of activated MIL-53 were added to a ball mill. The ball mill was sealed and evacuated, and argon was introduced and this operation was repeated 3 times. Then, the ball mill was milled in a ball mill for 1 hour (1000 rpm) to obtain a precursor powder. Ethanol was added to the precursor powder and centrifuged. The resulting precipitate was then centrifugally washed once with N,N-dimethylformamide and twice with ethanol, and then dried at 60°C for 12 hours to obtain sample 6.

[0046] Figure 1 The scanning electron microscope images of MIL-53 in Examples 1, 2, 3, 4, 5, 6 and 7 show that the obtained MIL-53 has an octahedral morphology and a uniform particle size.

[0047] Figure 2 This is a scanning electron microscope image of sample 1 in Example 2. It is observed that MIL-53 is destroyed by mechanical ball milling, and its surface is modified by Ni and Co-based inorganic salts and the particles are evenly distributed.

[0048] Figure 3 This is the transmission electron microscope image of sample 1 in Example 2, and it can be observed that the MOF particle size distribution is uniform.

[0049] Figure 4 This is a scanning electron microscope image of sample 3 in Example 4. It can be observed that the particle distribution of the obtained product is relatively uniform, and some particles are aggregated together.

[0050] Figure 5 This is a scanning electron microscope image of sample 6 in Example 7. It is observed that the particles of the obtained product are unevenly distributed, and most of the particles are in a piled state.

[0051] Figure 6 The electrocatalytic performance diagram of sample 1, sample 2, sample 3, sample 4, sample 5, sample 6, and RuO2 shows that, under the doping of different inorganic salts, the formed sample 1 (Fe / Co / Ni-MOFs) exposes more active sites and accelerates the mass transfer and transfer of charges. The current density is 10 mA cm -2 When the overpotential is only 180mV.

[0052] Figure 7 The electrochemical impedance spectra of sample 1, sample 2, sample 3, sample 4, sample 5, sample 6, and RuO2 show that sample 1 (Fe / Co / Ni-MOFs) formed under the doping of different inorganic salts exposes more active sites and accelerates the mass transfer and transfer of charges, minimizing its impedance value.

[0053] The present invention discloses an electrocatalytic material based on MOF and a preparation method thereof; the preparation method of the material comprises: forming a MIL-53 material by a solvothermal method, adding a metal source, and destroying the surface of the MIL-53 by a mechanical ball milling method so that the metal source is combined with the surface to form a Fe / Co / Ni-MOFs material. The Fe / Co / Ni-MOFs material formed by the mechanical ball milling method of the present invention solves the problems of poor conductivity and low electrocatalytic activity of the original MOF material. The prepared material has excellent electrocatalytic activity. In the electrocatalytic test, the current density is 10 mA cm -2 In this range, the overpotential is only 180mV.

[0054] The preferred embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. All experiments and technical solutions that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A MOF-based electrocatalytic material, characterized in that The MOF-based electrocatalytic material is prepared by the following method: The Fe-based MOFs are placed at 100-200° C. for 1-24 hours for activation to obtain activated Fe-based MOFs; under a protective atmosphere, the activated Fe-based MOFs, nickel salt and cobalt salt are ball-milled at 300-1500 rpm for 30-180 minutes; the obtained powder is subjected to post-treatment A to obtain the MOF-based electrocatalytic material; The mass ratio of the activated Fe-based MOFs, nickel salt and cobalt salt is 1:0.5-2:0.5-2.

2. The MOF-based electrocatalytic material according to claim 1, characterized in that: The protective atmosphere is argon, nitrogen or helium.

3. The MOF-based electrocatalytic material according to claim 1, characterized in that: The nickel salt is one of anhydrous nickel chloride, nickel acetate tetrahydrate, nickel nitrate hexahydrate, and nickel chloride hexahydrate, or a mixture of two or more thereof.

4. The MOF-based electrocatalytic material according to claim 1, characterized in that: The cobalt salt is one of cobalt acetate tetrahydrate, cobalt nitrate hexahydrate, and cobalt chloride hexahydrate, or a mixture of two or more thereof.

5. The MOF-based electrocatalytic material according to claim 1, characterized in that: The mass ratio of the activated Fe-based MOFs, nickel salt and cobalt salt is 1:1:

1.

6. The MOF-based electrocatalytic material according to claim 1, characterized in that: The Fe-based MOFs are one of MIL-53, MIL-88A, MIL-88B, MIL-100, MIL-101, NH2-MIL-53, NH2-MIL-88B, NH2-MIL-101, or a mixture of two or more thereof.

7. The MOF-based electrocatalytic material according to claim 6, characterized in that: The Fe-based MOFs is MIL-53.

8. The MOF-based electrocatalytic material according to claim 1, characterized in that: The post-treatment A is as follows: centrifuging the powder with ethanol, washing the obtained precipitate with N,N-dimethylformamide by centrifugation, washing with ethanol by centrifugation, and drying to obtain the MOF-based electrocatalytic material.

9. Use of the MOF-based electrocatalytic material as claimed in claim 1 in an electrocatalytic reaction.

10. The use according to claim 9, characterized in that: The electrocatalytic reaction is an electrocatalytic oxygen evolution reaction.

Citation Information

Patent Citations

  • Multi-metal MOFs derived oxygen reduction / oxygen evolution double-function catalytic material, and preparation method thereof

    CN109926084A

  • Fe-doped novel two-dimensional Co-MOFs composite material as well as preparation method and application thereof

    CN114736388A